Global, regional, and national burden and quality of care index (QCI) of lip and oral cavity cancer: a systematic analysis of the Global Burden of Disease Study 1990-2017 - Ahmad Sofi-Mahmudi; Masoud Masinaei; Erfan Shamsoddin; Marcos Roberto Tovani-Palone; Mohammad-Hossein Heydari; Shervan Shoaee; Erfan Ghasemi; Sina Azadnajafabad; Shahin Roshani; Negar Rezaei; Mohammad-Mahdi Rashidi; Reyhaneh Kalantar Mehrjardi; et al. (BMC, 2021)
Abstract Background To measure the quality of care for lip and oral cavity cancer worldwide using the data from the Global Burden of Disease (GBD) Study 2017. Methods After devising four main indices of quality of care for lip and oral cavity cancer using GBD 2017 study's measures, including prevalence, incidence, years of life lost, years lived with disability, and disability-adjusted life years, we utilised principal component analysis (PCA) to determine a component that bears the most proportion of info among the others. This component of the PCA was considered as the Quality-of-Care Index (QCI) for lip and oral cavity cancer. The QCI score was then reported in both men and women worldwide and different countries based on the socio-demographic index (SDI) and World Bank classifications. Results Between 1990 and 2017, care quality continuously increased globally (from 53.7 to 59.6). In 1990, QCI was higher for men (53.5 for men compared with 50.8 for women), and in 2017 QCI increased for both men and women, albeit a slightly higher rise for women (57.2 for men compared with 59.9 for women). During the same period, age-standardised QCI for lip and oral cavity cancer increased in all regions (classified by SDI and World Bank). Globally, the highest QCI scores were observed in the elderly age group, whereas the least were in the adult age group. Five countries with the least amount of QCIs were all African. In contrast, North American countries, West European countries and Australia had the highest indices. Conclusion The quality of care for lip and oral cavity cancer showed a rise from 1990 to 2017, a promising outcome that supports patient-oriented and preventive treatment policies previously advised in the literature. However, not all countries enjoyed such an increase in the QCI to the same extent. This alarming finding could imply a necessary need for better access to high-quality treatments for lip and oral cavity cancer, especially in central African countries and Afghanistan. More policies with a preventive approach and paying more heed to the early diagnosis, broad insurance coverage, and effective screening programs are recommended worldwide. More focus should also be given to the adulthood age group as they had the least QCI scores globally.